2015
DOI: 10.2147/ccid.s86863
|View full text |Cite
|
Sign up to set email alerts
|

In vitro inhibition of hyaluronidase by sodium copper chlorophyllin complex and chlorophyllin analogs

Abstract: BackgroundInhibitors of hyaluronidase are potent agents that maintain hyaluronic acid homeostasis and may serve as anti-aging, anti-inflammatory, and anti-microbial agents. Sodium copper chlorophyllin complex is being used therapeutically as a component in anti-aging cosmeceuticals, and has been shown to have anti-hyaluronidase activity. In this study we evaluated various commercial lots of sodium copper chlorophyllin complex to identify the primary small molecule constituents, and to test various sodium coppe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 16 publications
0
28
0
Order By: Relevance
“…Personal care and beauty industries have the ability to improve Saudi import and export transactions and market (e.g., Banaja Saudi Import Company, Spimaco, Tabuk Pharmaceutical and Biotechnology Manufacturing and Al-Jazeera Pharmaceutical Industries), population income growth, employment and increasing the appetites for quality healthcare and hygiene under the regulation, supervision and coordination Saudi Food and drug Authority (SDFA) and other government stakeholders agencies [6,8,24,25,32,39,40]. The prediction showed that new ingredients will continue to be developed in this sector locally from plant, animal and marine sources [1,2,27,33,41].…”
Section: Benefits Of Local Cosmeceuticals Stakeholders Partnership Anmentioning
confidence: 99%
See 4 more Smart Citations
“…Personal care and beauty industries have the ability to improve Saudi import and export transactions and market (e.g., Banaja Saudi Import Company, Spimaco, Tabuk Pharmaceutical and Biotechnology Manufacturing and Al-Jazeera Pharmaceutical Industries), population income growth, employment and increasing the appetites for quality healthcare and hygiene under the regulation, supervision and coordination Saudi Food and drug Authority (SDFA) and other government stakeholders agencies [6,8,24,25,32,39,40]. The prediction showed that new ingredients will continue to be developed in this sector locally from plant, animal and marine sources [1,2,27,33,41].…”
Section: Benefits Of Local Cosmeceuticals Stakeholders Partnership Anmentioning
confidence: 99%
“…Forecasting cosmeceutical industries growth and performance in enhancing beauty and personal care will continue to conditioning considerably the cosmeceutical industry, however the outpaced of digital and media marketing will provide stronger value growth worldwide [27,33,41]. It is expected that Saudi cosmetics market growth will continue due to the growing traditional and western lifestyle young population, rising disposable income, leading domestic and international stakeholders, substantial government expenditures and strong economic growth [23,28,36].…”
Section: Forecasting the Future Of Cosmeceutical Industries Developmentmentioning
confidence: 99%
See 3 more Smart Citations